Kekerasan, trauma, dan kritik terhadap tradisi dalam alih wahana Di Tubuh Tarra, dalam Rahim Pohon - Ramadhani, Arga Dara; Hapsarani , Dhita (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
The narrative of child violence and trauma in the adaptation of Faisal Oddang’s short story Di Tubuh Tarra, dalam Rahim Pohon into the @budayakita podcast reveals the complex interplay between tradition and the realities of contemporary society. This study aims to examine the transformation of the narrative of violence and child trauma through Gerard Genette’s narratological framework and Judith Herman’s trauma theory. Employing a textual analysis method, the research identifies shifts in narrative structure that emerge during the adaptation process. The findings indicate that mothers and children occupy vulnerable positions within the dominant social system. The narrative transformation from short story to podcast amplifies a critical stance toward patriarchal structures that perpetuate harm against women and children. This study concludes that the short story to podcast conversion of Di Tubuh Tarra, dalam Rahim Pohon not only illustrates the struggle of children in the face of violence but is also expected to contribute to the discussion of literary research that focuses on child abuse.